Prevalence of Hypertension and Diabetes in Elderly Residents of Kahrizak - Farshad Sharifi; Mojde Mirarefin; Hossein Fakhrzadeh; Soheil Saadat; Maryam Ghaderpanahi; Zohre Badamchizade; Ahmadali Akbarikamrani (University of Social Welfare & Rehabilitation Sciences, 2009)
Objectives: The aim of the present study was to investigate the prevalence of hypertension and type II diabetes in elderly Iranianresidents of the Kahrizak Charity Foundation (KCF). Methods & Materials: In this cross-sectional study, a total of two hundred sixty eight men and women ≥60 years were studied. The data were collected during annual health examination of the elderly residents in KCF. Hypertension and diabetes were defined based on JNC VII andAmerican Diabetes Association, respectively. Results: Crude prevalence of hypertension was 55% in men and 67% in women. In hypertensives, mean age and Body Mass Index (BMI) were significantly higher than normotensives. Diabetes prevalence was 21% in men and 16% in women. Means of age, body mass index (BMI), waist to hip ratio (WHR), total cholesterol, LDL-cholesterol in diabeticwere significantly more than normal ones. Conclusion: Body mass index and hypertension showed significant correlation and women were at higher risk for hypertension. Instead,men were at higher risk of diabetes and its related factors.